Grating based pressure monitoring system for subaquatic application - Mathias, Regina; Ambalgi, Ambresh P.; Upadhyaya, Anup M. (International journal of information technology (Singapore. Online), 2018)
In this work we proposed fibre Bragg grating (FBG) based pressure sensor, to detect the pressure in subaquatic application. For specific underwater pressure intervals, change in wavelength of FBG sensor is simulated with photonic design software. Obtained results exhibited distinct shift in peak resonant wavelength with wavelength ranging from 1550 to 1556 nm with Q factor of 1,32,280. FBG encapsulated mechanical model designed and analyzed to investigate strain behavior due to pressure application. Pressure and strain change values are overlapping for the operable wavelength of 1.5625 during mechanical and optical analysis. Absolute sensitivity of sensor found to be 0.04644/RIU. This proposed sensor can play significant roles in studying underwater diving conditions.